First Report of Buchwaldoboletus lignicola (Boletaceae), a Potentially Endangered Basidiomycete Species, in South Korea. Issue 4 (2nd October 2019) - Jo, Jong Won; Kwag, Young-Nam; Cho, Sung Eun; Han, Sang-Kuk; Han, Jae-Gu; Lim, Young Woon; Sung, Gi-Ho; Oh, Seung Hwan; Kim, Chang Sun
Abstract: During the 2014 survey of the mushroom flora of Gwangneung forest in South Korea, we collected two specimens of boletoid mushroom growing on a felled tree of Pinus koraiensis . These specimens were characterized by a light brown to reddish-brown pileus with appressed tomentum, pore surface bluing instantly when bruised, golden-yellow mycelium at the base of stipe, and lignicolous habitat. Both specimens were identified as Buchwaldoboletus lignicola, a rare basidiomycete, based on morphological characteristics and sequences of internal transcribed spacer (ITS; fungal barcode). Here, we describe these specimens and provide the first report of this genus in South Korea.